Of Monkeys and Men: Immunomic Profiling of Sera from Humans and Non-Human Primates Resistant to Schistosomiasis Reveals Novel Potential Vaccine Candidates - Pearson, Mark S.; Becker, Luke; Driguez, Patrick; Young, Neil D.; Gaze, Soraya; Mendes, Tiago; Li, Xiao-Hong; Doolan, Denise L.; Midzi, Nicholas; Mduluza, Takafira; McManus, Donald P.; Wilson, R. Alan; et al. (Frontiers in Immunology, 2015)
Schistosoma haematobium affects more than 100 million people throughout Africa and is the causative agent of urogenital schistosomiasis. The parasite is strongly associated with urothelial cancer in infected individuals and as such is designated a group I carcinogen by the International Agency for Research on Cancer. Using a protein microarray containing schistosome proteins, we sought to identify antigens that were the targets of protective IgG1 immune responses in S. haematobium-exposed individuals that acquire drug-induced resistance (DIR) to schistosomiasis after praziquantel treatment. Numerous antigens with known vaccine potential were identified, including calpain (Smp80), tetraspanins, glutathione-S-transferases and glucose transporters (SGTP1), as well as previously uncharacterized proteins. Reactive IgG1 responses were not elevated in exposed individuals who did not acquire DIR. To complement our human subjects study, we screened for antigen targets of rhesus macaques rendered resistant to Schistosoma japonicum by experimental infection followed by self-cure, and discovered a number of new and known vaccine targets, including major targets recognised by our human subjects. This study has further validated the immunomics-based approach to schistosomiasis vaccine antigen discovery and identified numerous novel potential vaccine antigens.